PENGARUH POLA KOMUNIKASI DALAM KELUARGA TERHADAP PERKEMBANGAN BAHASA ANAK USIA 4-6 TAHUN - Widya Puteri, Ika Apriati; Trunoyudho, Etna Anjani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Language development is an indicator of a child's cognitive development, and delays in this have an impact on various functions in their life. Communication between parents and children will be an important stimulus in children's language development. Communication patterns in the family describe the family's tendency to develop fairly consistent and predictable ways of communicating with each other. This patterns have two dimensions, which is conversation orientation and conformity orientation. Errors in parental communication can have an impact on the achievement and quality of development of children's language skills. Children may reach language benchmarks and construct sentences at appropriate levels, but unable or less able to discuss things with other children or with adults. The purpose of this research is to determine the influence of family communication patterns on the language development of children aged 4-6 years. The research was conducted with 50 respondents using the Language Development Scale instrument adapted from the Denver Developmental Screening Test II to measure children's language development, and using the Revised Family Communication Patterns Parent's Version to measure family communication patterns. The research results showed that there was an influence of family communication patterns on the language development of children aged 4-6 years (p=0.000) of 23.4% (R Square=0.234).